The starter garden handbook : a cook's guide to growing your own food - Alvrez, Alice (Coral Gables, FL : Mango Publishing Group, a division of Mango Media Inc., 2018)
Here in one pretty package is everything you need to know to have your garden and eat it, too! Whether you aspire to green rookie level, eco-master or full-on gardening guru , you can lean to grow your own food and help the planet every week of the year.--
Includes bibliographical references (page 134).
Keywords: Organic gardening; Vegetable gardening; Herb gardening; Herb gardening; Organic gardening; Vegetable gardening